Network signal coverage expansion planning WLAN outdoor with 4-C scenario approach at Telkom University - Rayhan Sidiq Kaffa; Zhikya Sekar Lutfi Purnomo; Rangga Fadhillah Akbar; Uke Kurniawan Usman; Sakti Putro Wisetyo (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2026)
Enhancing internet accessibility on campus is vital for both academic purposes and general internet usage. This research aims to expand the outdoor WiFi coverage at Telkom University, taking into account wireless signal propagation, infrastructure, and network structure. The planning process includes conducting a walk test to evaluate signal coverage, simulating signal and interference, calculating the link budget (including pathloss, RSSI, and EIRP), and determining the Bill of Quantities (BoQ). The analysis of these simulations and calculations leads to informed planning recommendations. By applying the 4-C scenario approach, the study demonstrates that this method effectively covers the entire target area with a minimum RSSI of -75 dBm. There is no interference in the 2.4 GHz band, although co-channel interference occurs in the 5 GHz band. The RSSI consistently stays above -75 dBm, with the lowest measurement being -74 dBm over 200 meters in the 2.4 GHz band. EIRP values are within Indonesia's standard limit of 36 dBm, with a peak value of 33 dBm in the 5 GHz band. The total length of transmission cables used is 1628.3 meters, and the total BoQ amounts to Rp. 384,964,540.